Functional outcome of operative treatment for pelvic metastatic bone disease from primary thyroid cancer: A case series. (2020) - Prabowo, Yogi; Asril, Elfikri; Wikanjaya, Rio
Highlights: 70 % of all malignant bone tumors are metastatic in origin. Functional outcome of MBD surgical management rarely described in literature. SF-36 and MSTS can be used to measure the functional outcome of MBD surgery. Surgery remains a good choice of therapy for MBD of pelvic. Abstract: Background: Metastatic bone disease (MBD) is the most common malignancy of bone. It is estimated that 70 % of all malignant bone tumors are due to metastasis. The functional outcome from pelvic MBD surgical management has been rarely described in the literature contrary to that of the long bones. Method: We reported three patients that underwent pelvic resection surgery due to pelvic MBD. All of the primary tumors were thyroid cancer. We measure the functional outcome using SF-36 and MSTS (musculoskeletal tumor society) scores after a one-year follow-up. Result: The SF-36 scoring result was that all of the patients had a remarkable improvement in terms of pain (77.5 %, 100 %, and 100 %). All of the patients also still had proper social functioning (75 %, 100 %, and 100 %) and good emotional well-being (72 %, 92 %, and 88 %). According to the MSTS, the second and third case had an excellent functional outcome; however the first case had poor functional outcome Conclusion: Surgery remains the choice of therapy for pelvic MBD that results in alleviation of pain and quality of life improvement.